Art and Truth in Aristotle’s Thought - Nikas, Vasilios (Conatus - Journal of Philosophy, 2018)
Very much unlike Plato, who believes that art is three steps away from truth, Aristotle in his Nicomachean Ethics defines art as a creative habit accompanied by true reason; in other words, truth and art are interrelated according to Aristotle. According to contemporary scholars, and due to the potential of mimesis, art is considered to be a tendency towards unveiling the eternal absolutes. In this paper I will discuss art in the light of the Aristotelian approach, that is, as a broadening of what is real and essential, and as an unmediated, unexpected, and instant intuitive understanding of the truth in all its simplicity and wholeness.